(untitled) (Jurnal Proaksi, 2025)
Main Purpose Mining companies are encouraged to make detailed disclosures through sustainability reports and implement corporate social responsibility. This research aims to determine effect disclosure of sustainability reports, corporate social responsibility and company performance on tax avoidance. Method - This research a quantitative approach and data processing using linear regression method with a sample of 10 mineral subsector companies for the 2021-2023 period. The research sample was determined based on the purposive sampling method. This research uses data analysis techniques, namely descriptive statistical, classical assumption and multiple linear regression. Main Findings - The research findings indicate that the disclosure of the sustainability report and company performance have a significant positive effect on tax avoidance. Corporate social responsibility has a significant negative effect on tax avoidance. Company performance has a positive influence on tax avoidance. Theory and Practical Implications - The results of this study provide a theoretical contribution by demonstrating that the disclosure of sustainability reports and company performance can have a positive relationship with tax avoidance practices, while CSR shows a negative influence. Novelty - In previous studies, the relationship between sustainability reports, corporate social responsibility, and company performance has often been discussed partially, considering these aspects in a more holistic manner. The researcher is interested in further exploring the impact of sustainability report disclosure, corporate social responsibility, and company performance on tax avoidance, with a specific and relevant focus on mineral sub-sector mining companies listed on the Indonesia Stock Exchange during the period 2021–2023. Keywords: sustainability report, corporate social responsibility, Firm Perfomance, tax avoidance.